PENGARUH PENGETAHUAN, TRUST DAN KEMUDAHAN PENGGUNAAN E-BANKING TERHADAP MINAT BERTRANSAKSI SECARA ONLINE - Sari Hasbullah, Indah; Ramadhan, Abid; Suardi, Ahmad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The title of article is the effect of Knowledge, trust and ease of use e-banking in online transactions. This study aims to specify the effect of Knowledge, trust and ease of use e-banking in online transactions. The data collection method used is the questionnaires distributed direcly to the costumers of bank Muamalat KC Palopo. The type of data used in this study is primary data. Sampling in this study using accidental sampling technique, amounting to 50 people who are customers of Bank Muamalat KC Palopo. This study uses a quantitative approach (statistics) using multiple linear regression analysis, based on the outcomes of this study indicating that the knowledge variable does not have a posistive effect on the interest in online transactions, the trust variable positively impacts the interest in online transactions, and the variable ease of use e-banking does not positively effect the interest in online transactions. The coefficient of determination shows that knowledge, trust, and ease of use of e-banking affect online transactions by 47.1%, while the rest is influenced by other factors outside this study.